The Influence of Digital Marketing, Entrepreneurial Orientation, Business Innovation, and Competitive Advantage on Business Sustainability with Customer Satisfaction as a Mediating Variable - Widiya Selfiyana; Pahrudin; Muh. Fahrurrozi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of digital marketing, entrepreneurial orientation, business innovation, and competitive advantage on business sustainability with customer satisfaction as a mediating variable in MSMEs in East Lombok. This study uses a quantitative approach with an explanatory design. The research sample consisted of 150 respondents consisting of MSME owners or managers who have used digital marketing in their business activities. The sampling technique used purposive sampling, while data collection was carried out through distributing questionnaires using a Likert scale. Data analysis was carried out using SPSS through validity and reliability tests, multiple linear regression, and Sobel mediation tests. The results of the study indicate that digital marketing, entrepreneurial orientation, business innovation, and customer satisfaction have a positive and significant effect on business sustainability, while competitive advantage does not have a significant direct effect on business sustainability. In addition, customer satisfaction is able to mediate the influence of digital marketing, business innovation, and competitive advantage on business sustainability, but is unable to mediate the influence of entrepreneurial orientation on business sustainability. This research confirms that the sustainability of MSME businesses is greatly influenced by the ability of business actors to utilize digital technology, create innovation, and increase customer satisfaction in a sustainable manner.